Adaptation of Six Sigma Method in Software Development - H, Aditya Pai; Dash, Chimaya; Behera, Prakash; , Piyush Kumar Pareek (International Journal of Computer Sciences and Engineering, 2025)
The six sigma is used in targeting the business process of the organization by reducing and fixing the defects being occurred by driving the six standard deviations among the mean and its specification limit, which is why it is known to be six. The research study of the paper suggests the application aspect in the software development that are proven to be eliminating the final defects from the overall products be delivered thus by reducing the variations.